Fatores associados ao consumo de álcool e outras drogas por pessoas transgênero no estado do Espírito Santo - Moreira, Juliana Almeida (2023)
The term transgender (TRANS) includes people whose gender identity and/or expression differs from cultural expectations based on the sex assigned to them at birth. This group experiences higher rates of harassment and bullying, homelessness, sexual and physical violence, parental rejection and social isolation when compared to cisgender people (CIS). Such negative experiences, combined with the lack of social support, put these people at substantial risk of abusing substances as a coping mechanism for the stress suffered. In this context, the present study aimed to identify the differences in the consumption of alcohol and other drugs between TRANS and CIS people and to identify the factors associated with the consumption of alcohol and other drugs by TRANS people. This is a cross-sectional observational analytical study involving participants recruited through an electronic link, who answered questionnaires through an online platform that included socioeconomic, health, depressive symptoms, quality of life and alcohol consumption and other variables. drugs. The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) screening tool was the instrument used to detect the use of alcohol, tobacco and other psychoactive substances. Simple linear regression analysis was fitted in three models to verify the association between explanatory variables associated with the use of alcohol and other drugs by TRANS people. A significance level of 5% was considered for all tests. The sample included 145 individuals (66 TRANS and 79 CIS). The median age of participants in the TRANS was 23 (18-44) years and in the CIS 24 (19-57) years (p>0.05). The group of CIS volunteers had a lower proportion of participants who received <1 minimum wage (MW) (p=0.001) and a higher proportion with complete higher education and/or postgraduate studies (p=0.003). Regarding the experience of prejudice, it was higher among TRANS people (p≤0.001). Most TRANS had some comorbidity (p=0.004), smoked (p<0.001) and had depressive symptoms compared to CIS volunteers (p<0.001). Consumption of alcohol, tobacco, marijuana, cocaine, amphetamines, hypnotics and hallucinogens was higher in the TRANS group (p<0.05 for all). Linear regression analyzes showed that being TRANS increases the score for tobacco consumption (β= 4,851; CI= 2,567 -7,135; p≤0,001), marijuana (β= 3,700; CI= 1,717 - 5,684; p=≤0,001) and hallucinogens (β= 0.886; CI= 0.227 - 1.546; p=0.009). When assessing income across gender identity categories (TRANS woman, TRANS man and non-binary), it was observed that a large proportion of non-binary volunteers received less than 1 MW (p=0.004) compared to the other categories . On the other hand, most of the non-binary participants in the sample did not use hormone therapy (p=0.022). The consumption of hallucinogens was higher among non-binary individuals (p=0.021). Multivariate linear regression analysis revealed that students and/or unemployed (β= -3,082; CI= -5,964 – -0,200; p=0,037) and who underwent sex reassignment surgery (β= -6,864; CI= -11,368 – -2,361; p=0,003) showed negative associations with alcohol consumption. Likewise, those categorized as students and/or unemployed (β= -7,754; CI= -11,624 – -3,884; p=0≤0.001), who did not experience transphobia (β= -8,603; CI= -14,656 – -2,551 ; p=0.006) and who had low body dissatisfaction (β= -3,866; CI= -7,531 – -0.201; p=0.039) showed negative associations with tobacco consumption. On the other hand, those who had completed higher education were positively associated with the consumption of hypnotics (β= 2.349; CI= 0.736 – 3.962; p=0.005). In addition, those self-identified as brown and/or black were positively associated with the consumption of other drugs (β= 1.435; CI= 0.307 – 2.562; p=0.014). The results of this study revealed that a significant portion of the TRANS population is exposed to the abuse of alcohol and other drugs. Furthermore, skin color, income, experiences of prejudice and the presence of comorbidities have been shown to interfere with the consumption of these harmful substances. There is a need to implement measures to identify drug abuse and promote adequate and targeted intervention in the context of the specific needs of this population group. As well as the promotion of greater actions and public health policies aimed at this public, as variables such as income, education, presence of comorbidities, body satisfaction and access to health services can influence the greater or lesser consumption of alcohol and other drugs.